1997
DOI: 10.1212/wnl.49.5.1424
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensory event-related potentials in response to trigeminal and olfactory stimulation in idiopathic Parkinson's disease

Abstract: Decrease of olfactory function in patients with Parkinson's disease (PD) has been reported by several authors. The current study investigated olfaction in PD patients using olfactory event-related potentials (OERPs) as an electrophysiologic correlate of olfactory function in combination with psychophysical testing. A specific focus was the influence of antiparkinsonian drugs. We investigated PD patients treated with antiparkinsonian drugs (n = 13) and PD patients who received no pharmacologic treatment (n = 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
1
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(53 citation statements)
references
References 15 publications
4
43
1
5
Order By: Relevance
“…The P1 response is thought to correlate with activity at the olfactory bulb and P3 with the olfactory cortex. The time to these intervals in PD has been shown to be clearly slowed without reduction in amplitude [4,29,30] . Limiting the use of OERPs is electroencephalography contamination by slow wave activity, patient compliance required by long (30-40 s) interstimulus intervals and the difficulty of interpreting a negative OERP in the setting of functional anosmia [31] .…”
Section: Assessing Smell Loss In Pdmentioning
confidence: 99%
“…The P1 response is thought to correlate with activity at the olfactory bulb and P3 with the olfactory cortex. The time to these intervals in PD has been shown to be clearly slowed without reduction in amplitude [4,29,30] . Limiting the use of OERPs is electroencephalography contamination by slow wave activity, patient compliance required by long (30-40 s) interstimulus intervals and the difficulty of interpreting a negative OERP in the setting of functional anosmia [31] .…”
Section: Assessing Smell Loss In Pdmentioning
confidence: 99%
“…In patients with PD, electrophysiological studies have shown that olfactory event-related potentials have prolonged latencies when compared to controls, whereas amplitudes are of a similar magnitude [Barz et al, 1997;Hawkes et al, 1997]. MEG studies of olfactory information processing have so far not been performed in patients with PD.…”
Section: Introductionmentioning
confidence: 99%
“…Of the sensory impairments associated with PD, olfactory impairment has received most attention. PD patients exhibit impairments in odor detection, identification, and discrimination (2-6) and a reduced olfactory evoked response (7,8). This occurs so consistently that the olfactory impairment may have diagnostic value for PD (9)(10)(11)(12).…”
mentioning
confidence: 99%